Fishing for the unknown: exploring current issues within Singapore's fishery sectors - Yang, Gavin Wen Kai (Nanyang Technological University, 2023)
The future of Singapore’s seafood security faces uncertainty as fish stocks dwindles in our neighbouring countries’ waters, affecting their ability to export seafood. As such, Singapore launched the “30-by-30” initiative to boost aquaculture production, propelling the nation’s ability to self-produce local nutritional needs. Despite this increased attention on Singapore’s seafood scene, knowledge gaps remain within the environmental and business sustainability aspect of the imported wild-caught and aquaculture sector. This includes supply chain disruptions, our seafood imports’ traceability, and financial and environmental constraints. To fill in these knowledge gaps and help improve our fishery sector management, a qualitative study was conducted using ethnography and interviews with stakeholders involved in both sectors. Here, we found that global events affected seafood import supply chains, but the main culprit for soaring local seafood prices were Singapore's rising living costs, forcing fish traders to change business models. Additionally, traceability of our seafood imports is poor as details of how they travel through the supply chain remains unknown. Next, fish farmers are hesitant to adopt long-term improvements as they are cost-inefficient in the short-term. These adaptations would alleviate issues such as the destructive effects of HABs and rising electricity and fish feed prices. The farmers have a short-term gain mindset as they are unconfident about their business longevity as renewal of their faming leases remain uncertain. Despite the “30-by-30” initiative, Singapore's future of local seafood production remains shaky due to fish farmers' unwillingness and inability to afford the costs required to upscale long-term aquaculture production.